1988
DOI: 10.1002/clc.4960110903
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit pectin inhibits hypercholesterolemia and atherosclerosis in miniature swine

Abstract: Summary:We studied the effect of dietary grapefruit pectin on plasma cholesterol and the development of atherosclerosis in 18 miniature swine. Pigs were randomized to one of three diets: no added fat (I), added fat/cellulose (11), and added fat/pectin (III). Plasma cholesterol was measured monthly. Arteries were examined for atherosclerosis at the termination of the experiment. Pectin supplementation of an added fat diet resulted in a significantly lower average plasma cholesterol than did cellulose supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…Interestingly, supplementation with pectin or inulin did not affect atherogenic diet-induced changes in blood parameters such as cholesterol. These findings are in contrast to those obtained by other authors, who reported beneficial effects of pectin on circulating cholesterol in pigs and humans [42,43,54,55]. It is tempting to speculate that 5% of pectin used in the current study was too low.…”
Section: Plos Onecontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, supplementation with pectin or inulin did not affect atherogenic diet-induced changes in blood parameters such as cholesterol. These findings are in contrast to those obtained by other authors, who reported beneficial effects of pectin on circulating cholesterol in pigs and humans [42,43,54,55]. It is tempting to speculate that 5% of pectin used in the current study was too low.…”
Section: Plos Onecontrasting
confidence: 99%
“…For the ADp group, 5% pectin (agroPECT-A 100/70, agro Food Solution GmbH, Werder, Germany) was added to the atherogenic diet. In the ADi group, 5% inulin (Orafti 1 IPS; Beneo GmbH, Tienen, Belgium) was added according to literature [36,43,44,54]. The feed was provided ad libitum.…”
Section: Feed Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Beakey et al (1988) reported that grapefruit pectin reduced atherosclerosis in miniature swine [27]. McCall et al (1992) compared the intake of low-cholesterol cellulose (LCC), high-cholesterol psyllium (HCP), and high-cholesterol cellulose (HCC) in African green monkeys for 3.5 years and reported that both LCC and HCP significantly reduced blood cholesterol than HCC and that dietary psyllium decreased total blood cholesterol by decreasing LDL cholesterol synthesis [28,29].…”
Section: Fiber Blood Cholesterol and Atherosclerosismentioning
confidence: 99%
“…Animal studies have suggested that pectin can inhibit dietinduced hypercholesterolemia without lower ing HDL [82], Cerda et al [83] demonstrated the regression or prevention of atherosclerosis in microswine with chronic hypercholesterol emia. This reduction in atherosclerosis was independent of the serum cholesterol levels.…”
Section: Lipids Cardiovascular Disease and Hypertensionmentioning
confidence: 99%